Modern And Classic Wound Dressing Comparison In Wound Healing - Rafika Nur Siregar (International Journal of Medicine and Health, 2024)
Wound care has also developed rapidly after the dissemination of the concept of TIME (Tissue, Infection, Moisture, and Wound Edge) in modern dressing (MD). The aim of this study was to compare modern dressings (MDs) and classic dressings (CDs) in terms of patient comfort, cost effectiveness and wound healing. A prospective study design with total of 25 participants. The sampling technique used was consecutive sampling. Patient comfort was assessed through the frequency of wound care and pain scale using the Visual Analogue Scale (VAS). Cost-effectiveness was assessed using direct and indirect costs. Wound healing was assessed using the Bates-Jensen Wound Assessment Tool (BWAT) score. The data was analyzed using the independent t and Mann-Whitney tests. The application of MD has the same cost-effectiveness as CD with a more satisfactory outcome for the wounds in terms of comfort and healing.